REPRESENTASI KHILAFAH DALAM PEMERINTAHAN REPUBLIK SPIRITUAL - Nurkhalis, Nurkhalis (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2018)
Abstract Khilafah cut off after the Ottoman Caliphate so that is no longer found of the Islamic government in the modern era. Then al-Afghani and M. Abduh reappeared the khilafah to the expression of wahdat al-Islamiyah which idea’s Rashid Ridha turned to a new term into Pan Islamism. This study is a literature study (library research) where the source data obtained from books of khilafah and Islamic government thinkers. Data were analyzed using critical interpretation analysis methods from Khomeini and al-Juwaini's thoughts including data reduction, data exposure, and conclusion. Based on the accumulation of theory among others Al-Mawdudi made it possible to divert Islamic rule to democracy. Hasan al-Banna socialized the return system of the khilafah. Ibn Khaldun hinted that the breaking of the Caliphate signifies that every state has a final period of government so that the caliphate system will not be permanent until the state fell in the territorial nations. Iqbal criticizes Islam not nationalism and even imperialism but the commonwealth nations without racial and demarcation. Al-Shatibi maintains the spirit of the maqashid shari'ah in the Islamic government. Imam Khomeini switched to the wilayat al-faqih. Ibn Taymiyya states that the complexity of establishing the Islamic Government is as complex as determining Islamic scholars. Al-Juwaini offers a solution to the concept of ghiyatsi namely the government that emphasizes the shari'ah that continues to be discussed in searching for the best format. The modern era is certainly running the Islamic Government only through the government of the spiritual republic by not lifting ahlu zimmah (non Muslim), ahlu kitab, munafiq (hipocrit), zindiq (orientalist), dayyus, musyrik (idolatry), dahriyyun (atheis), ashab'ah (naturalist) become government leaders. Preferred leaders who have be ahl muruwwah (authority) ie people who have previous life records in a measurable and open goodness in the public space for executive, legislative and judicial candidates performed fit and proper test by people who have the same religious knowledge with the fuqaha. Keywords: Khilafah, Islam, Government, and Spiritual Republic Abstrak Khilafah terputus pasca Khalifah Utsmaniyah sehingga hampir tidak ditemukan lagi bentuk Pemerintahan Islam di era modern. Kemudian al-Afghani dan M. Abduh merekonstruksi khilafah kepada Wahdat al-Islamiyah yang kemudian Rashid Ridha mengalihkan ke istilah baru menjadi Pan Islamisme. Kajian ini dilakukan melalui studi kepustakaan di mana sumber datanya diperoleh dari buku dan kitab dari pemikir khilafah dan pemerintahan Islam. Data dianalisis dengan menggunakan metode analisis interpretasi kritis dari pemikiran Khomeini dan al-Juwaini meliputi reduksi data, pemaparan data dan penarikan kesimpulan. Akumulasi teori pemerintahan Islam dari beberapa intelektual Islam diantaranya Al-Maududi memungkinkan pergeseran pemerintahan Islam ke demokrasi. Hasan al-Banna mengajak mensosialisasikan pengembalian sistem khilafah. Ibnu Khaldun mengisyaratkan terputusnya khilafah menandakan setiap negara memiliki masa akhir pemerintahan menyebabkan sistem khilafah tidak akan permanen hingga terbentuk negara dalam territorial bangsa-bangsa. Iqbal mengkritisi Islam bukan nasionalisme bahkan imperialisme melainkan bangsa-bangsa persemakmuran tanpa rasial dan demarkasi. Al-Shatibi mempertahankan adanya ruh maqashid syari‘ah dalam pemerintahan Islam. Imam Khomeini beralih berpedoman kepada wilayah al-faqih. Ibnu Taimiyah menyatakan bahwa dharurat mendirikan Pemerintahan Islam sebagaimana dharurat menentukan ahli Islam. Al-Juwaini menawarkan solusi kepada konsep ghiyatsi yakni pemerintahan yang mementingkan syari‘at yang terus didiskusikan dalam mencari format yang terbaik. Era modern kepastian menjalankan Pemerintahan Islam hanya melalui pemerintahan republik spiritual dengan tidak menjadikan ahlu zimmah (non muslim), ahlu kitab, munafiq, musyrik, dahriyyun (atheis), ashab’ah (naturalis) menjadi pemimpin pemerintahan. Pemimpin diutamakan yang mempunyai ahl muruwwah (kewibawaan) yakni orang yang memiliki catatan hidup sebelumnya dalam kebaikan yang terukur dan terbuka di ruang publik bagi kandidat eksekutif, legislatif dan yudikatif dilakukan fit and proper test oleh orang yang memiliki religius yang sama ilmunya dengan fuqaha. Kata Kunci: Khilafah, Islam, Pemerintahan, dan Republik Spiritual